1981
DOI: 10.1038/bjc.1981.3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of lymphocytotoxicity to autochthonous leukaemic cells in chronic myeloid leukaemia

Abstract: Summary.-Lymphocytes from 13 chronic myeloid leukaemia (CML) patients in remission were tested for their ability to differentiate in vitro into a cell population cytotoxic to autochthonous target leukaemic cells. CML remission lymphocytes were cultured in vitro with autochthonous leukaemic cells and allogeneic normal lymphocytes from an unrelated donor, singly or in combination. The cytotoxic lymphocytes obtained after 7 days of culture were tested for their ability to kill autochthonous leukaemic cells in a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For the Vg target ( Figure IA) IFN treatment of effector cells alone resulted in a The doses found suitable for enhancement of NK cell-mediated lysis of fresh human leukaemia cells were lower than the ActD concentrations of 40 pg ml-1 used by Schlager et al (1979) for enhanced complement-dependent lysis of a guinea pig hepatoma, but they are comparable to the lugml-l dose used by Kunkel et al (1981) for the enhancement of NK cell-mediated lysis of murine fibroblasts.…”
Section: Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the Vg target ( Figure IA) IFN treatment of effector cells alone resulted in a The doses found suitable for enhancement of NK cell-mediated lysis of fresh human leukaemia cells were lower than the ActD concentrations of 40 pg ml-1 used by Schlager et al (1979) for enhanced complement-dependent lysis of a guinea pig hepatoma, but they are comparable to the lugml-l dose used by Kunkel et al (1981) for the enhancement of NK cell-mediated lysis of murine fibroblasts.…”
Section: Cellsmentioning
confidence: 99%
“…Treatment of the fibroblasts with cycloheximide or Actinomycin D, however, induces strong NK cell mediated lysis. (Collins et al, 1981;Kunkel & Welsh, 1981). In vitro derived carcinogen-transformed fibroblasts were highly NK sensitive, but again became resistant when passaged in mice with high NK cell activity (Collins et al, 1981).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier studies we demonstrated that lymphocytes from chronic myeloid leukaemia (CML) patients in remission react to leukaemiaassociated antogens in vitro (Gangal et al, 1976(Gangal et al, , 1979Khare et al, 1981). When a small group of patients was followed up through 2nd and 3rd cycles of relapse and remission, it was observed that leukaemia associated in vitro immune reactivity was negatively correlated with the progress of the disease (Gangal et al, 1977).…”
mentioning
confidence: 98%